Offering the right incentive at the right time: Leveraging customer mental accounting to promote prepaid service. (March 2022) - Qiu, Shangzhi; Wu, Laurie; Yang, Yanjia; Zeng, Guojun
Abstract: The current study investigates promotional techniques to improve the sales of prepaid service. Drawing on mental accounting theory, this research examines the impacts of two promotional factors, namely incentive type and promotion timing, on consumers' intentions to purchase prepaid services. The results of studies reveal that a discount (vs. a bonus) is more effective in enhancing consumers' purchase intentions, given higher associated levels of perceived incentive value. Moreover, offering the promotion after (vs. before) payment leads to stronger purchase intention due to lower perceived cost. However, the advantage of a discount over a bonus is attenuated when the promotion is offered after (but not before) payment. Highlights: Prepaid service promotional techniques are investigated. Discount is more effective than bonus to drive up prepaid service sales. Offering the deal after (vs. before) check payment is more effective in promotion. Advantage of discount is mitigated when the deal is offered after (vs. before) check payment.